Advanced textile materials : selected, peer reviewed papers from the 2011 International Conference on Textile Engineering and Materials (ICTEM 2011), September 23-25, 2011, Tianjin, China - Liu, Huawu; Qian, Xiaoming (Advanced materials research ;, 2011)
Volume is indexed by Thomson Reuters CPCI-S (WoS)This book, comprising internationally peer-reviewed papers, covers the subject areas of natural fibers, chemical fibers, fiber manufacturing technology, principles of textile design, structure, properties and processing of textile materials, measurement technology and instrumentation, non-woven materials, structure, properties and processing of non-woven materials, coloration technology, finishing technology, pollution control and treatment of dyeing and finishing, materials and their applications, materials processing technologies and other related topics. The volume will be of interest to anyone working in these fields. The first volume in the three-volume set from the September 2011 conference reports new developments in fiber manufacturing technology, textile design, natural fibers, and chemical fibers. Several papers investigate the preparation of nanofibers by electrospinning. Volume two describes the structure and properties of textile materials, measurement instruments, non-woven materials, and coloration technology. The last volume addresses finishing technology, material processing, and pollution control with a pair of papers from the China University of Petroleum evaluating the treatment of polymerization effluents by multiscale membrane filtration, flocculation, and Fenton oxidation. Other topics of the 400+ papers include measuring the diameter of cashmere and wool, the structural characteristics of rabbit hair, the acoustical absorption coefficient of non-woven fabrics, and the advantages of a basalt glass flake coating for marine anti-corrosion.